Ultimate capability of variable pitch milling cutters. Issue 1 (2018) - Stepan, Gabor; Hajdu, David; Iglesias, Alex; Takacs, Denes; Dombovari, Zoltan
Abstract: Variable pitch milling cutters intend to increase performance, but off-the-shelf cutters do not ensure this generally. Depending on the milling process they are selected for, they can perform better or even worse than uniform pitch cutters do. Improved performance can be guaranteed by considering the reflected dynamic behaviour of the machine/tool/workpiece system. This work presents the achievable upper and lower capability bounds by introducing so-called stabilizability diagrams of a hypothetical variable pitch milling cutter that is tuned continuously along the stability boundaries. Robustly tuned milling cutters are designed for selected spindle speed ranges, which are experimentally tested both under laboratory and industrial conditions.